Pendampingan Desain Batik Ciprat Pada Komunitas Batik Ciprat Difabel Gadingan Desa Jombor Bendosari Sukoharjo - Salim Salim; Kustanto; Sutrisno; Dwi Remawati; Aninda Dyah Hayu P P; Amin Sulistiyowati; Usman Sabila Firdos (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
Splash batik is a form of batik innovation that has a unique visual character through a color splashing technique, resulting in abstract and artistic motifs. In addition to its cultural value, splash batik has also developed as a medium for creative economic empowerment, including for groups of people with disabilities. The Gadingan Disabled Batik Splash Community in Jombor Village, Bendosari District, Sukoharjo Regency, is a group of people with disabilities who actively produce splash batik to develop creativity and increase economic independence. However, in its implementation, several obstacles are still encountered, especially in aspects of motif design development, color combination exploration, and design variations that are not optimal, thus affecting the aesthetic value and competitiveness of the product. This community service activity aims to improve the ability of community members in developing splash batik designs through participatory design mentoring. The implementation method is carried out through several stages, namely observation and problem identification, program planning, splash batik design mentoring, design practice and exploration, and evaluation of activity results. The approach used emphasizes direct practice-based learning (learning by doing) so that participants can develop ideas and creativity independently. The results of the activity demonstrated an increase in community members' abilities in various design aspects. Evaluations showed an increase in motif creativity from 55% to 90%, color combination from 60% to 88%, design neatness from 65% to 87%, motif innovation from 50% to 85%, and creative confidence from 70% to 92% after the mentoring program. This activity had a positive impact on improving the aesthetic quality of ciprat batik products while also increasing the motivation of community members with disabilities to develop their creativity and produce more innovative works.